Influence of spatial confinements on the group velocities of acoustic phonons in PbI2 nanofilms - Lutsiuk, Yuriy; Kramar, Valeriy (Lviv : Ivan Franko National University, 2022)
Result of theoretical studies the group velocities of acoustic phonons in the qusi-2D nanosystems such as flat ultra-thin films, based on layer crystal 2H-PbI2 with hexagonal symmetry, is represented there.
Keywords: phonon, acoustic pphonon, group velocity, nanosystem, nanofilm